(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The automated monitoring of a building’s structural health during its exploitation is a way to extend its design life without compromising structural safety. In turn, it helps increase the rate of building renovation works compared to demolition works, which reduces future construction and demolition waste levels.This research explores the vibration-based global monitoring method application to structurally stiff medium-rise reinforced concrete buildings by analysing predicted building vibration amplitudes and spectrum under regular city traffic excitation. These predictions are based on the results obtained from finite element calculations of building models with variated structural stiffness and inertial mass of the building.Regular traffic-generated ground frequency spectrum differs from the first natural frequencies of medium-rise reinforced concrete buildings, and the vibration energy is low. Nevertheless, it is found that the structural identification of such building dynamic parameters is still possible, particularly natural frequencies. It was found that the ratio between fundamental frequency for the fixed base model of the building and elastic spring foundation model is the decisive parameter for selecting the building part to be monitored. Structural health monitoring vibration-based methods are also a promising technology for medium-rise mass house buildings when tailored according to some damage sensitive feature.